NILAI-NILAI KEARIFAN LOKAL DALAM KESEHARIAN AKTIVITAS PEMBELAJARAN ELEKTRONIK DI MASA PANDEMI COVID-19: BAGAIMANA GURU MENGONSTRUKSI KONTEN, SIKAP, DAN PERILAKU SISWA? - Sapikzal Pratama; Mubiar Agustin; Temmy Renaldi Setia Bakti (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aimed to explain how teachers construct local wisdom valuesin learning activities during the pandemic. This research used a case study method. Data was obtained by interview, observation and documentation study of the research subjects, namely four teachers who taught in different areas. From the interview results, it was known that teachers used local wisdom as learning content that was based on themes. The teacher used students’ daily journals to analyze students' attitudes and behaviors whether it was in accordance with the values and norms prevailing in the local area or not. Local wisdom supported character education, so it must be taught in a balanced manner both as content and as habituation of student attitudes and behavior.